-2m(m-1)=3(-m+80)

Simple and best practice solution for -2m(m-1)=3(-m+80) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2m(m-1)=3(-m+80) equation:


Simplifying
-2m(m + -1) = 3(-1m + 80)

Reorder the terms:
-2m(-1 + m) = 3(-1m + 80)
(-1 * -2m + m * -2m) = 3(-1m + 80)
(2m + -2m2) = 3(-1m + 80)

Reorder the terms:
2m + -2m2 = 3(80 + -1m)
2m + -2m2 = (80 * 3 + -1m * 3)
2m + -2m2 = (240 + -3m)

Solving
2m + -2m2 = 240 + -3m

Solving for variable 'm'.

Reorder the terms:
-240 + 2m + 3m + -2m2 = 240 + -3m + -240 + 3m

Combine like terms: 2m + 3m = 5m
-240 + 5m + -2m2 = 240 + -3m + -240 + 3m

Reorder the terms:
-240 + 5m + -2m2 = 240 + -240 + -3m + 3m

Combine like terms: 240 + -240 = 0
-240 + 5m + -2m2 = 0 + -3m + 3m
-240 + 5m + -2m2 = -3m + 3m

Combine like terms: -3m + 3m = 0
-240 + 5m + -2m2 = 0

Begin completing the square.  Divide all terms by
-2 the coefficient of the squared term: 

Divide each side by '-2'.
120 + -2.5m + m2 = 0

Move the constant term to the right:

Add '-120' to each side of the equation.
120 + -2.5m + -120 + m2 = 0 + -120

Reorder the terms:
120 + -120 + -2.5m + m2 = 0 + -120

Combine like terms: 120 + -120 = 0
0 + -2.5m + m2 = 0 + -120
-2.5m + m2 = 0 + -120

Combine like terms: 0 + -120 = -120
-2.5m + m2 = -120

The m term is -2.5m.  Take half its coefficient (-1.25).
Square it (1.5625) and add it to both sides.

Add '1.5625' to each side of the equation.
-2.5m + 1.5625 + m2 = -120 + 1.5625

Reorder the terms:
1.5625 + -2.5m + m2 = -120 + 1.5625

Combine like terms: -120 + 1.5625 = -118.4375
1.5625 + -2.5m + m2 = -118.4375

Factor a perfect square on the left side:
(m + -1.25)(m + -1.25) = -118.4375

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| t^2-8t-5=0 | | -75+25=-2x+12x | | 6=-2x+3x | | 3x-8=-6+x | | 6x-5x=8 | | -3(y+4)=18 | | -4x^3+10x=0 | | x*14+23=x*5+266 | | -2x+3+7x=-7 | | -4x^3+-10x=0 | | x^2+4x-98=0 | | 36y=7(5y-4) | | x*14+23= | | x*12+25=x*3+250 | | 6x-10-9x=5 | | 22=6(u+4)-4u | | 2x+4(x-3)=4 | | 4x(12x^2-4x)=0 | | 367=7(5y-4) | | 3x-3-5x=7 | | 4(y+5)+4y=20 | | 6x-5x=-9 | | 54-7x=2x+23 | | 9+6x=5x-10 | | 2z-1=3z+8 | | -7x+4=-6-8x | | 10-10x=48-17x | | -8x+7x=-8 | | 5x+4=8+7x | | 3b=5b | | 114-7x=20x+24 | | -10x+9x+2=-5 |

Equations solver categories